2023
DOI: 10.1017/flo.2022.35
|View full text |Cite
|
Sign up to set email alerts
|

Effect of aspect ratio on the propulsive performance of tandem flapping foils

Abstract: In this work, we describe the impact of aspect ratio ( $AR$ ) on the performance of optimally phased, identical flapping flippers in a tandem configuration. Three-dimensional simulations are performed for seven sets of single and tandem finite foils at a moderate Reynolds number, with thrust producing, heave-to-pitch coupled kinematics. Increasing slenderness (or $AR$ ) is found to improve thrust coefficients and thrust augmentation but the benefits level of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 75 publications
(107 reference statements)
0
1
0
Order By: Relevance
“…Tang et al [ 24 ] carried out a numerical study on the self-propulsion of 3D flutter flexible plates in stationary fluid by combining the immersion boundary lattice Boltzmann method and the finite element method, pointing out that proper structural flexibility can improve the propulsion speed and efficiency. Lagopoulos et al [ 25 ] revealed that increasing the aspect ratio can improve thrust coefficients and thrust augmentation by using a three-dimensional numerical simulation method. Kumar et al [ 26 ] used the fluid module of the ANSYS software to calculate the thrust generated by the active flapping motion in short waves.…”
Section: Introductionmentioning
confidence: 99%
“…Tang et al [ 24 ] carried out a numerical study on the self-propulsion of 3D flutter flexible plates in stationary fluid by combining the immersion boundary lattice Boltzmann method and the finite element method, pointing out that proper structural flexibility can improve the propulsion speed and efficiency. Lagopoulos et al [ 25 ] revealed that increasing the aspect ratio can improve thrust coefficients and thrust augmentation by using a three-dimensional numerical simulation method. Kumar et al [ 26 ] used the fluid module of the ANSYS software to calculate the thrust generated by the active flapping motion in short waves.…”
Section: Introductionmentioning
confidence: 99%